Isolated Hypogonadotropic Hypogonadism in a Young Woman with Primary Amenorrhoea - Zalkha Al Kharusi; Nadia Al Mabaihsi; Amani Al Rawahi; Abeer Al Hadhrami; Maisa Al Kiyumi; Almundher Al-Maawali; Abdulaziz Al Mahrezi (Oman Medical Journal)
We describe a case of a young woman who presented with delayed secondary sexual development and primary amenorrhoea. She had low levels of oestradiol, follicle-stimulating hormone, and luteinizing hormone with normal levels of other pituitary hormones. Genetic testing revealed a rare diagnosis of autosomal recessive hypogonadotropic hypogonadism 8. She was treated with hormone therapy to promote the growth of the uterus and secondary sexual characteristics. Combined contraceptive pills were initiated. A pelvis ultrasound taken after six months revealed a growing uterus.